INDUSTRIAL COMPETITIVENESS AS A BASIS OF SERBIAN REINDUSTRIALIZATION - Nikolic, Miroljub; Pokrajac, Slobodan; Filipović, Milorad; Filipović, Sonja; Vasić, Miloš (Journal of Applied Engineering Science, 2016)
This paper analyzes the issue of reindustrialization of Serbia, from the standpoint of industrial competitiveness. The authors believe that reindustrialization is necessary and possible only in those industries that have considerable potential for growth of competitiveness on the international market. The key assumptions for this are constant growth of innovation and productivity, as well as other factors that essentially rely on new knowledge and new technology. This development trend is present in all advanced economies, including the European Union, to which Serbia aspires. In recent years, reindustrialization has become an increasingly dominant development strategy on a global scale. It involves a very ambitious plan related to the development of modern and sophisticated, environmentally responsible and energy-efficient industries, especially manufacturing sectors, which employ highly professional workers and foster close cooperation with universities and research institutes. In this context, governments, rather than the markets, are becoming the main change drivers, as they can contribute to creating the necessary industrial “state of mind”, which implies new redistribution of tasks and effects of labor among the key stakeholders in the process of creating new values: employees, owners, government, science, education, etc.
Keywords: reindustrialization; new knowledge; Markets; Industry; competitiveness